Being an Indonesian Christian Examined Based on Matthew 28:19-20 - Friyanti, Vriska; Sukarna, Timotius (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study explores the origins and growth of Christianity in Indonesia, emphasizing its historical and theological significance through Matthew 28:19-20. Initially introduced by Western nations, Christianity has shaped Indonesia’s religious landscape. Using a qualitative descriptive approach and historical-theological analysis, this research examines Christianity’s integration into Indonesian culture and its role in nation-building. Data was collected from literature reviews of theological sources and historical accounts. Findings show that despite colonial origins, Christianity is now a core part of Indonesia’s pluralistic society. Future research should further explore integrating Christian principles into national development efforts